FULL TRANSFER FULL ACCESS MODEL IN THE ACQUISITION OF ENGLISH AS A FOREIGN LANGUAGE: A GENERATIVE GRAMMAR PERSPECTIVE - Dudung Gumilar; Dadang Sudana; Aceng Ruhendi Syaifullah (University of Kuningan, 2025)
This study investigates the acquisition of English wh-interrogative structures by Indonesian learners at the B2 level, focusing on the interaction between Wh-movement and Subject–Auxiliary Inversion (SAI) within the framework of Generative Grammar. Using a qualitative descriptive design, data were collected through an Elicited Grammaticality Judgment Test (EGJT) consisting of 18 wh-question items. The learners’ responses were analyzed syntactically to identify patterns of convergence and divergence in their Interlanguage Grammar (ILG), particularly in relation to the predictions of the Full Transfer Full Access (FTFA) model and the Minimal Trees Hypothesis (MTH). The findings reveal that the majority of learners successfully produced target-like interrogative structures characterized by both Wh-movement and SAI, indicating substantial acquisition of the CP system in English. However, a considerable number of responses exhibited partial structures, such as Wh-fronting without auxiliary inversion or auxiliary inversion without Wh-movement. These patterns suggest that while learners have largely acquired the abstract features of whquestions, the integration of syntactic operations remains gradual and developmental. Fully non-target structures were found only in a small proportion of the data, reflecting early or transitional stages of grammatical restructuring. The results strongly support the FTFA model, which assumes full transfer of L1 grammatical knowledge and continued access to Universal Grammar in second language acquisition. Learners’ ability to produce complex interrogative structures, even with occasional divergence, demonstrates that functional categories and feature-checking mechanisms remain active throughout development. In contrast, the Minimal Trees Hypothesis fails to adequately explain the presence of target-like CP structures observed in the data. Overall, the study confirms that interlanguage development in English wh-questions is systematic, rule-governed, and driven by gradual parameter resetting rather than by the absence of functional syntax.